(untitled) (The South East European Journal of Economics and Business, 2023)
The paper examines the relationship between different sources of funding for research and development at universities. Following the European Commission methodology, we distinguished between government, business and abroad financing of research and development (R&D) in the higher education sector. The paper aims to test short-run and long-run relationships between different funding sources. We are focused on the relationship between government and business funding of R&D at universities. Based on panel data for EU countries, we applied the Granger causality tests and General methods of moments to examine short-run causality and cointegrating regression to search for potential long-run relationships. Our results suggest that government funding of R&D act as a complement to business funding. Hence, rising government financial support for research in higher education can, lead to higher funding from the business sector. Founding from abroad seems to have a similar effect on business funding in the long run